Catena - Justus Liebig-Universität Giessen. Geographisches Institut; International Society of Soil Science; International Union of Soil Sciences (Elsevier Science Pub. Co., 1973)
"An interdisciplinary journal of pedology, hydrology, geomorphology."
Keywords: Geomorphology : Periodicals; Hydrology : Periodicals; Soil science : Periodicals; Geology, Structural : Periodicals; Soils : Periodicals